2022
DOI: 10.31083/j.fbl2707206
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Polyphenol-Rich Fraction of Boesenbergia rotunda in Diabetic Rats: A Focus on Hypoglycemic, Antihyperlipidemic, Carbohydrate Metabolism, Antioxidant, Anti-Inflammatory and Pancreato-Protective Activities

Abstract: Introduction: Boesenbergia rotunda is a famous culinary/medicinal herb native to Southeast Asia region and it is traditionally used in the treatment of several diseases. This study investigated the anti-diabetic properties of Boesenbergia rotunda polyphenol extract (BRE) in high fructose/streptozotocin-induced diabetic rats. Method: The in vitro antioxidant activity was evaluated using DPPH and ABST colorimetric assays, while the Folin-Ciocalteu method was used for the total phenolic content of BRE. For diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…These glycation end products have been proposed to be responsible for corneal and other ocular complications arising from uncontrolled DM 34 . HbA1C is an early glycation end product, and its assay is used to diagnose prolonged diabetes and to assess control of glycemia in diabetic individuals 35 , 36 . In addition, it has been reported that DM with increased HbA1C concentrations predisposes the cornea to epithelial barrier dysfunction, leading to corneal complication 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These glycation end products have been proposed to be responsible for corneal and other ocular complications arising from uncontrolled DM 34 . HbA1C is an early glycation end product, and its assay is used to diagnose prolonged diabetes and to assess control of glycemia in diabetic individuals 35 , 36 . In addition, it has been reported that DM with increased HbA1C concentrations predisposes the cornea to epithelial barrier dysfunction, leading to corneal complication 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that STZ diabetes model leads to impairment of the ß-cells of the pancreas, leading to decreased synthesis and release of insulin into circulation. Additionally, it has been established that insulin resistance and decreased insulin secretion are key parameters that contribute to the onset of DM 36 . These might therefore explain the decreased circulating insulin and increased HOMA-IR values in the diabetic group 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of caspases occurs approximately a half day after cisplatin treatment in vitro (5), and suppressing the activity of caspase reduced cisplatin-induced apoptosis (6,7). A previous study reported that Boesenbergia rotunda could stimulate the generation of osteoblast cells (8) and significantly increase pancreatic antioxidant enzyme activities (glutathione, superoxide dismutase, and catalase) (9). Considering the antioxidant property and the activity of B. rotunda in inducing cells growth, our present study aimed to investigate the cytotoxicity of cisplatin on human embryonic kidney-293 (HEK-293) cells and the protective impact of the ethanol extract of B. rotunda (EEBR) against such conditions by quantifying the expression of Kim-1, NGAL, nuclear factor-kappaB (NF-κB), caspase-3, and caspase-7 genes in cisplatin-exposed HEK-293 cells.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, B. rotunda has prominent anticancer, antioxidant, anti-inflammatory, anti-apoptotic wound healing, antiulcer, antidiabetic and antibacterial effects 16 19 . B. rotunda polyphenolics especially flavonoids and chalcone derivatives are the major bioactive compounds in the plant accounting for the reported bioactivity of the plant 15 , 20 , 21 . Regarding the antioxidant and anti-inflammatory properties of B. rotunda , it has been shown that B. rotunda suppressed lipid peroxidation, protein kinase B (Akt) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-KB), while simultaneously increasing antioxidant defense 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…B. rotunda polyphenolics especially flavonoids and chalcone derivatives are the major bioactive compounds in the plant accounting for the reported bioactivity of the plant 15 , 20 , 21 . Regarding the antioxidant and anti-inflammatory properties of B. rotunda , it has been shown that B. rotunda suppressed lipid peroxidation, protein kinase B (Akt) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-KB), while simultaneously increasing antioxidant defense 20 , 21 . However, the efficacy of B. rotunda against DOX-induced cardiac toxicity has not been explored.…”
Section: Introductionmentioning
confidence: 99%